1988
DOI: 10.3109/03630268808998033
|View full text |Cite
|
Sign up to set email alerts
|

Identification by Fast Atom Bombardment Mass Spectrometry of HB Indianapolis [β112(G14)CYS→ARG] in a Family from Naples, Italy

Abstract: We have characterized a P112 Arg hemoglobin in an individual from Naples, Italy, with minimal clinical problems.Blood tests revelead only slight reticulocytosis and hemoglobin instability. Furthermore, high value of alkali resistance tests for Hb F were observed. Isoelectricfocusing of globins showed the occurrence of a band migrating between the normal a and P globin chains. The fairly stable variant chain was purified by fast protein liquid chromatography. A mass map of the tryptic digest was obtained by fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This mutant was initially described as Hb Indianapolis (b112 Cys ! Arg) (Adams et al 1979), which was subsequently reported in two families (Spanish and Italian) (Baiget et al 1986;De Biasi et al 1988) in whom affected members had evidence of mild hemolytic anemia with 2% -4% reticulocytosis. In two patients heterozygous for Hb Terre Haute, globin-chain biosynthesis studies showed an a:non-a ratio of 1.0 in bone marrow erythroblasts compared with a ratio of 2.0 in peripheral blood reticulocytes.…”
Section: Missense Mutationsmentioning
confidence: 95%
“…This mutant was initially described as Hb Indianapolis (b112 Cys ! Arg) (Adams et al 1979), which was subsequently reported in two families (Spanish and Italian) (Baiget et al 1986;De Biasi et al 1988) in whom affected members had evidence of mild hemolytic anemia with 2% -4% reticulocytosis. In two patients heterozygous for Hb Terre Haute, globin-chain biosynthesis studies showed an a:non-a ratio of 1.0 in bone marrow erythroblasts compared with a ratio of 2.0 in peripheral blood reticulocytes.…”
Section: Missense Mutationsmentioning
confidence: 95%
“…To date, three Hb variants with amino acid substitutions at the 112th position of the β chain have been reported: Hb Yahata, Hb Toranomon and Hb Indianapolis (11)(12)(13)(14)(15)(16)(17). In this case, Hb Yahata [β112 TGT (Cys) TAT (Tyr)] (heterozygote) was diagnosed.…”
Section: Discussionmentioning
confidence: 82%
“…Patients heterozygous for Hb Indianapolis [β 112 (G14) Cys Arg] reportedly have a very unstable variant with a phenotype similar to that of severe β-thalassemia (15). However, members of a Spanish family heterozygous for that variant were not anemic, despite exhibiting positive results on an in vitro test for unstable Hb (16). Hb Indianapolis was recently reported to cause moderate hemolytic anemia and renal damage in a Brazilian patient (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the`real' Hb Indianapolis (b112 Cys ! Arg) has subsequently been reported in two families (Spanish and Italian) in whom affected members had evidence of mild haemolytic anaemia with 2±4% reticulocytosis (Baiget et al, 1986;De Biasi et al, 1988). Hb Indianapolis was mildly unstable and the b variant formed 41±43% of the total b-globin chains.…”
Section: Molecular Basismentioning
confidence: 97%